Molecular Pathopharmacology of 5-HT2C Receptors and the RNA Editing in the Brain - Michihisa Tohda; Michio Nomura; Yasuyuki Nomura (Elsevier, 2006)
Abstract.: Among the 14 kinds of serotonin (5-hydroxytryptamine, 5-HT) receptor subtypes (5-HTR), 5-HT2C receptor (5-HT2CR) has been intensively investigated because of its physiologically and pathophysiologically important role in the brain. 5-HT2CR has been suggested to be involved in depressive disorders based on findings from pharmacological/neurochemical/behavioral studies using autopsy preparations of humans suffering from depression, animal models of depression, and animals treated with antidepressant drugs. Recently the editing of 5-HT2CR mRNA has been reported to participate in the pathogenesis of depressive disease. The RNA editing of 5-HT2CR induced by the presumable alteration of deaminase during a pathological state in depression causes changes of a base to another base (e.g., adenosine to guanosine, cytidine to uracil (thymidine)), followed by changes in amino acids constituting the second intracellular transmembrane loop that couples G proteins. Thus 5-HT2CR receptor-mediated signal transduction is changed. In the present review, the pathopharmacological significance of 5-HT2CR in special reference to RNA editing of receptors is reviewed and discussed from the aspect of development of novel therapeutics for depression. Keywords:: 5-HT2C receptor, RNA editing, depression, antidepressant